2016
DOI: 10.1002/clc.22496
|View full text |Cite
|
Sign up to set email alerts
|

Gender, Racial, and Health Insurance Differences in the Trend of Implantable Cardioverter‐Defibrillator (ICD) Utilization: A United States Experience Over the Last Decade

Abstract: Prior studies have highlighted disparities in cardiac lifesaving procedure utilization, particularly among women and in minorities. Although there has been a significant increase in implantable cardioverter-defibrillator (ICD) insertion, socioeconomic disparities still exist in the trend of ICD utilization. With the use of the Nationwide Inpatient Sample from 2003 through 2011, we identified subjects with ICD insertion (procedure code 37.94) and cardiac resynchronization defibrillator (procedure code 00.50, 00… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
35
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 25 publications
5
35
1
1
Order By: Relevance
“…While white beneficiaries were much more likely to receive HD, all non-white subpopulations, including Asians who enjoy comparable IIV uptake, were much less likely to receive HD versus SD, as were beneficiaries with a Part D subsidy or residing in a rural region, populations arguably in more need of this more protective intervention. These results comport with well-documented disparities in dissemination of medical innovation reflecting multiple results [22][23][24][25][26]. Several factors correlated with higher IIV uptake, including having one or more comorbidities, ambulatory physician visits, or part D prescriptions, and having received a pneumonia vaccine, as has been previously observed [27].…”
Section: Discussionsupporting
confidence: 77%
“…While white beneficiaries were much more likely to receive HD, all non-white subpopulations, including Asians who enjoy comparable IIV uptake, were much less likely to receive HD versus SD, as were beneficiaries with a Part D subsidy or residing in a rural region, populations arguably in more need of this more protective intervention. These results comport with well-documented disparities in dissemination of medical innovation reflecting multiple results [22][23][24][25][26]. Several factors correlated with higher IIV uptake, including having one or more comorbidities, ambulatory physician visits, or part D prescriptions, and having received a pneumonia vaccine, as has been previously observed [27].…”
Section: Discussionsupporting
confidence: 77%
“…The ratio for ICDs between both genders is even 4:1 in favour of male patients and the ratio equally persists in all five investigated countries. Similarly, surprising results regarding the gender differences have also been found in previous large-scale studies (8,9). The authors of these studies claim that observed gender disparities could not be attributable to different heart failure prevalence across gender, different proportions of male and female subgroups in study samples, or to any other similar contextual factors, which might indicate that cardiologists adhere to different standards and/or guidelines while treating either male or female patients.…”
Section: Discussionmentioning
confidence: 65%
“…2 For example, ICD utilization in the United States has been reported to be 280 per million, in comparison to 4.3 per million in China and 3.1 per million in India. 3,4 Risk factors known to represent the severity of ventricular dysfunction and thus increase the risk of SCD include syncope or presyncope, [5][6][7] low ventricular ejection fraction (LVEF, ,25%), 8 nonsustained ventricular tachycardia (NSVT), [9][10][11] and frequent premature ventricular contractions (PVCs, 10/h). 12,13 In a retrospective analysis of the OMNI study, Assessing Therapies in Medtronic Pacemaker, Defibrillator and Cardiac Resynchronization Therapy Devices (ClinicalTrials.gov ID: NCT00277524), a subset of patients with PP indications with at least 1 of these risk factors had a similar rate of ventricular tachyarrhythmias (ventricular tachycardia or fibrillation [VT/VF]) as patients receiving ICDs for SP.…”
Section: Introductionmentioning
confidence: 99%